A clinical approach to the threat of emerging influenza viruses in the Asia‐Pacific region. Issue 7 (5th July 2017) - Hui, David S.C.; Lee, Nelson; Chan, Paul K.S.
ABSTRACT: Seasonal influenza epidemics and periodic pandemics are important causes of morbidity and mortality. Patients with chronic co‐morbid illness, those at the extremes of age and pregnant women are at higher risks of complications requiring hospitalization, whereas young adults and obese individuals were also at increased risk during the A(H1N1) pandemic in 2009. Avian influenza A(H5N1) and A(H7N9) viruses have continued to circulate widely in some poultry populations and infect humans sporadically since 1997 and 2013, respectively. The recent upsurge in human cases of A(H7N9) infections in Mainland China is of great concern. Sporadic human cases of avian A(H5N6), A(H10N8) and A(H6N1) have also emerged in recent years while there are also widespread poultry outbreaks due to A(H5N8) in many countries. Observational studies have shown that treatment with a neuraminidase inhibitor (NAI) for adults hospitalized with severe influenza is associated with lower mortality and better clinical outcomes, especially when administered early in the course of illness. Whether higher than standard doses of NAI would provide greater antiviral effects in such patients will require further investigation. High‐dose systemic corticosteroids were associated with worse outcomes in patients with severe influenza. There is an urgent need for developing more effective antiviral therapies for treatment of influenza infections.